STUDY OF RESPONSIVITY PERFORMANCE AND HEAT ABSORPTION POTENTIAL OF COCONUT OIL AS THERMAL ENERGY STORAGE MEDIUM IN INDONESIA - FAHMI (NIM : 90213007), ZULFIKAR
Electrical energy consumption is now large enough especially in big cities in Indonesia. Increased consumption of electrical energy occurs mainly due to the use of the air conditioning system (AC system) in the room. However, the electrical energy consumption of the air conditioning system can be reduced with the use of thermal energy storage system. Thermal energy storage system works in two ways: sensible and latent heats storage. Latent thermal energy storage system work more effective rather than the sensible heat storage system because it can save relatively large amount of heat through the solid-liquid phase transition process of the material. Coconut oil works can work as a thermal energy storage system as the alternative use of AC system because it has the melting temperature around the human thermal comfort zone in the tropical area. This research focused on the study of the responsiveness of coconut oil in various size containers and its potential use as a medium in the thermal energy storage system in Indonesia. Study for the responsiveness of coconut oil (Method I) were performed for two initial states of coconut oil, namely solid and liquid. Study of the potential heat absorption of coconut oil (Method II) was conducted to test the effect of mass quantities and container sizes of coconut oil for the air temperature in the thermal chamber. The results show that coconut oil with the smallest size of container (8 cm) is the most effective as seen from the average gradient and time delay analyses. In addition, there is a working range of latent temperature of coconut oil with that appropriate size for its application. The results for Method II show that the mass of coconut oil greatly affects its ability to absorb the heat, which is characterized by a decrease in the value of the air temperature. In more detail, the mass amount of coconut oil needed to decrease one degree Celsius of air temperature is around 0.96 kg, for the air temperature in the range of about 39 Ã‚Â°C. On the other hand, the container size of coconut oil plays a role in the amount of specimens that undergo solid-liquid phase transition during the heat absorption process.